Rancang Bangun Aplikasi Smart Kids English Berbasis Mobile - Dasuki, Moh; Abdurrahman, Ginanjar (INFORMAL: Informatics Journal, 2023)
Smart Kids English is a mobile-based learning media application that aims to help teachers and parents accompany children in learning English with different experiences by utilizing technology. The use of learning software is considered more effective because basically children use gadgets more often in their daily activities. Using learning software on gadget devices can also minimize the use of gadgets for unimportant applications such as playing games. The System Development Life Cycle in this research uses the Waterfall method, this method is used by many software developers. This research produces the Smart Kids English application with several basic features such as: pronunciation which is equipped with attractive images. Smart Kids English is equipped with a writing feature to train children in writing English. Smart Kids English is equipped with an animal sounds feature to increase children's insight into recognizing animal sounds in the environment around us. Smart Kids English is also equipped with a practice menu, the aim of which is to sharpen children's memory in remembering the material they have studied.